2016
DOI: 10.4103/jisp.jisp_218_16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of well-controlled type 2 diabetes mellitus on quality of life of chronic periodontitis patients

Abstract: Background:The purpose of the study is to examine the quality of life (QoL) in chronic periodontitis (CP) patients associated with or not with well-controlled type 2 diabetes mellitus (DM2).Materials and Methods:Five hundred CP patients, 250 with DM2 (GDM2 group) and 250 age- and gender-matched controls without DM2 (GND), were enrolled in this cross-sectional case-controlled study from January to September 2015. They were interviewed by a QoL questionnaire (Functional Assessment of Chronic Illness Therapy-Fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The bidirectional relationship between systemic diseases such as type 2 diabetes mellitus and periodontal disease has been the topic of numerous clinical researches in periodontal medicine. It also stands out that periodontal disease is the most prevalent oral complication in type 2 diabetes mellitus patients and it is considered the sixth classic diabetes complication (LORENTZ et al, 2009;MOURÃO et al, 2016;GUO et al, 2017). Such affirmations corroborate the findings of the present study, which confirm that generalized gingivitis is more prevalent (score 2) in diabetic patients, along with the fact that such patients presented a lower number of sextants with periodontal health than non-diabetics.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The bidirectional relationship between systemic diseases such as type 2 diabetes mellitus and periodontal disease has been the topic of numerous clinical researches in periodontal medicine. It also stands out that periodontal disease is the most prevalent oral complication in type 2 diabetes mellitus patients and it is considered the sixth classic diabetes complication (LORENTZ et al, 2009;MOURÃO et al, 2016;GUO et al, 2017). Such affirmations corroborate the findings of the present study, which confirm that generalized gingivitis is more prevalent (score 2) in diabetic patients, along with the fact that such patients presented a lower number of sextants with periodontal health than non-diabetics.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes mellitus is not considered the direct cause of periodontal disease, but rather a systemic factor that provides local conditions for its development, and bacterial plaque is the primary factor for developing periodontal disease (CHANG et al, 2013). However, in patients with DM2 associated with periodontal disease, a negative relationship with quality of life is observed (MOURÃO et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…12 Some studies have identified associations between oral pathology and DM2, 1,8,13,14 and both are associated with a worse perceived GH 15 and worse oralhealth quality of life due to OH manifestations. [16][17][18] The self-perception of health (SPH) is a subjective indicator that complements the clinical health status, independently of medical interpretations of signs and symptoms, and has been identified as an important predictor of mortality or health care. The SPH is a valid assessment of the individual's GH and OH perception [19][20][21][22] and can be used as a predictor of future health outcomes 23,24 or related to OH in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%